RELATIONSHIP BETWEEN SLEEP DISTURBANCE AND DEPRESSION, ANXIETY, AND FUNCTIONING IN COLLEGE STUDENTS - Nyer, Maren; Farabaugh, Amy; Fehling, Kiki; Soskin, David; Holt, Daphne; Papakostas, George I.; Pedrelli, Paola; Fava, Maurizio; Pisoni, Angela; Vitolo, Ottavio; Mischoulon, David (Depression and anxiety, 2013)
Background Sleep disturbance (SD) has complex associations with depression, both preceding and following the onset and recurrence of depression. We hypothesized that students with depressive symptoms with SD would demonstrate a greater burden of comorbid psychiatric symptoms and functional impairment compared to students with depressive symptoms without SD. Methods During a mental health screening, 287 undergraduate students endorsed symptoms of depression (Beck Depression Inventory [BDI] ≥ 13) and filled out the following self‐report measures: demographic questionnaire, BDI, Anxiety Symptom Questionnaire—intensity and frequency (ASQ), Beck Hopelessness Scale (BHS), Beck Anxiety Inventory (BAI), Quality of Life Enjoyment and Satisfaction Questionnaire (QLESQ), and the Massachusetts General Hospital Cognitive and Physical Functioning Questionnaire (CPFQ). SD was measured using the BDI sleep item #16 dichotomized (score 0: no SD; or score > 0: some SD). Results Students with depressive symptoms and SD (n = 220), compared to those without SD (n = 67), endorsed significantly more intense and frequent anxiety and poorer cognitive and physical functioning. Students with depressive symptoms with and without SD did not significantly differ in depressive severity, hopelessness, or quality of life. Conclusions College students with depressive symptoms with SD may experience a greater burden of comorbid anxiety symptoms and hyperarousal, and may have impairments in functioning, compared to students with depressive symptoms without SD. These findings require replication.